Efficacy study of Quantity Surveying Smart Learning Kit (QS2LK) - Siti Asmiza Muzafar,; Muhamad Azry Khoiry, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The utilization of the Quantity Surveying Smart Learning Kit (QS2LK) was developed to make it easier for students to gain knowledge through the use of three-dimensional (3D) drawings. The introduction to this development is focused on the problems faced by some Diploma of Quantity Surveying in Polytechnic students who find the design of building elements taught in the classroom difficult to understand. A product of creativity will address the problem of students who are less familiar with building structures to make quantity measurements in order to get a better understanding of the layout and design of building elements. The aim of the project is to assist the process of teaching and learning in the measurement of the quantities of building works and to define the usefulness of using the QS2LK. This kit examines the use of technology as compared to conventional approaches of teaching and learning processes. The kit requires a study of teaching and learning technology in general and questionnaire outcomes. The findings revealed that there was a significant difference before and after using the kit. Furthermore, the measurement subject’s achievement was higher before using it. While using QS2LK, this method of learning for all students taking Building Works Measurement subject will be more structured and easier to understand. In conclusion, the utilization of the developed smart learning kit enhanced students’ measurement skills and improved the measurement achievement.